DESCRIPCIÓN DE LA MORFOLOGÍA DENTAL Y DEL HÁBITO ALIMENTARIO DEL BESOTE JOTURUS PICHARDI (MUGILIFORMES: MUGILIDAE) (Boletín de Investigaciones Marinas y Costeras, 2016)
The dental morphology of J. pichardi and its relation to dietary habits is described for the fist time. This mugilid inhabits the torrential rivers of short course in the Sierra Nevada de Santa Marta, that quickly lead into the Caribbean Sea. Joturus pichardi has heterodont dentition, with different forms that vary according to the tooth containing structure. The observed tooth structure is typical of omnivorous fihes, and consistent with the structure and composition of the diet analyzed. The latter was found dominated by mosses and aquatic macro invertebrates, mainly Chironomidae, a family of Diptera.